INFORMATION AND INFORMATION PLANNING SYSTEM (Annual of the Faculty of Philosophy in Skopje, 2012)
Having a timely opportune, precise and revisioned information on disposal means achieving a certain advantage, respectively, if the correct information is used in the aproppriate time and on an aproppriate way, then it can be the most powerful weapon in the hands of the one that possesses it. In other words, having a precise and fast information means that the planned tasks will be realized completely and that information as some kind of data for a certain situation, selected, analyzed and interpreted will have the leading role in delivering certain decisions. The efficiency of the planning process depends in a great extent on information, or lack of information. Hence, it is not the same what kind of information a certain institution receives, nor the answer is accidential of how a certain institution after receiving the necessary information will act and how it will be used, because, from these presumptions the functioning of the institution itself depends in a large degree.
Keywords: INFORMATION; INFORMING; INFORMATION SYSTEM; PLANNING; PLANNING PRODUCTS